Laterally Heterogeneous 2D Layered Materials as an Artificial Light‐Harvesting Proton Pump. (15th June 2020) - Quan, Di; Ji, Danyan; Wen, Qi; Du, Linhan; Wang, Lili; Jia, Pan; Liu, Dan; Ding, Liping; Dong, Huanli; Lu, Diannan; Jiang, Lei; Guo, Wei
Abstract: Heterogeneous structures in nacre‐mimetic 2D layered materials generate novel transport phenomena in angstrom range, and thus provide new possibilities for innovative applications for sustainable energy, a clean environment, and human healthcare. In the two orthogonal transport directions, either vertical or horizontal, heterostructures in horizontal direction have never been reported before. Here, a 2D‐material‐based laterally heterogeneous membrane is fabricated via an unconventional dual‐flow filtration method. Negatively and positively charged graphene oxide multilayers are laterally patterned and interconnected in a planar configuration. Upon visible light illumination on the bipolar nanofluidic heterojunction, protons are able to move uphill against their concentration gradient, functioning as a light‐harvesting proton pump. A maximum proton concentration gradient of about 5.4 pH units mm −2 membrane area can be established at a transport rate up to 14.8 mol h −1 m −2 . The transport mechanism can be understood as a light‐triggered asymmetric polarization in surface potential and the consequent change in proton capacity in separate parts. The implementation of photonic–ionic conversion with abiotic materials provides a full‐solid‐state solution for bionic vision and artificial photosynthesis. There is plenty of room to expect the laterally heterogeneous membranes for new functions and better performance in the abundant family of liquid processable colloidal 2D materials. Abstract : Laterally heterogeneous 2D layered materials are fabricated via an unconventional dual‐flow filtration method. Two (or more) different types of colloidal 2D nanomaterials can be laterally patterned and interconnected in a planar multilayer configuration. Upon visible light illumination, protons are able to move uphill against their concentration gradient, functioning as an artificial light‐harvesting proton pump.